2022
DOI: 10.1093/mmy/myac058
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen and nitrogen species are crucial for the antifungal activity of amorolfine and ciclopirox olamine against the dermatophyte Trichophyton interdigitale

Abstract: Onychomycosis is a nail infection caused by Trichophyton interdigitale and other fungi, which can be treated with topical amorolfine (AMR) and ciclopirox olamine (CPX). Although these drugs are widely used, little is known about the role of reactive oxygen (ROS) and nitrogen (RNS) in their mechanism of action. Aiming to better understand the effects of AMR and CPX in dermatophytes, we evaluated whether they act through the production of ROS and peroxynitrite (PRN). We tested a set of strains, all susceptible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Most MIC values of other antifungals used to treat dermatophytosis are usually low. Specifically, studies revealed that the MIC of CPX ranges from 0.25 to 8 mg/L [ 32 , 33 ]. High inhibitory concentrations can lead to greater use of drugs in pharmaceutic formulations and undesirable effects.…”
Section: Discussionmentioning
confidence: 99%
“…Most MIC values of other antifungals used to treat dermatophytosis are usually low. Specifically, studies revealed that the MIC of CPX ranges from 0.25 to 8 mg/L [ 32 , 33 ]. High inhibitory concentrations can lead to greater use of drugs in pharmaceutic formulations and undesirable effects.…”
Section: Discussionmentioning
confidence: 99%